2007
DOI: 10.1007/bf02977648
|View full text |Cite
|
Sign up to set email alerts
|

cytotoxic germacranolide sesquiterpene lactones fromCarpesium triste var.manshuricum

Abstract: Four known germacranolide sesquiterpene lactones, 2alpha,5-epoxy-5,10-dihydroxy-6alpha-angeloyloxy-9beta-isobutyloxy-germacran-8alpha,12-olide (1), 2alpha,5-epoxy-5,10-dihydroxy-6alpha,9beta-diangeloyloxy-germacran-8alpha,12-olide (2, divaricin B), 2alpha,5-epoxy-5,10-dihydroxy-6alpha-angeloyloxy-9beta-(2-methylbutyloxy)-germacran-8alpha,12-olide (3) and 2alpha,5-epoxy-5,10-dihydroxy-6alpha-angeloyloxy-9beta-(3-methylbutyloxy)-germacran-8alpha,12-olide (4), were isolated from the chloroform-soluble fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Compounds 10 – 14 were identified as (2 S , 4 R , 5 R , 6 R , 7 S , 8 S , 9 R , 10 S , 2″ R ) -2,5-epoxy-5,10-dihydroxy-6-angeloyloxy-9-2-methylbutyryloxy-germacran-8,12-olide ( 10 ) 14 , 25 , 26 , (2 S , 4 R , 5 R , 6 R , 7 S , 8 S , 9 R , 10 S , 2″ S )-2,5-epoxy-5,10-dihydroxy-6-angeloyloxy-9-2-methylbutyryloxy-germacran-8,12-olide ( 11 ) 14 , 25 , 26 , (2 S , 4 R , 5 R , 6 R , 7 S , 8 S , 9 R , 10 S )-2,5-epoxy-5,10-dihydroxy-6-angeloyloxy-9-angeloyloxy-germacran-8,12-olide ( 12 ) 8 , 14 , 25 , 26 , 2 α ,5-epoxy-5,10-dihydroxy-6 α -angeloyloxy-9 β -3-methylbutyryloxy-germacran-8,12-olide ( 13 ) 18 20 , 25 , 26 , and 2 α ,5-epoxy-5,10-dihydroxy-6 α -angeloyloxy-9 β -isobutyryloxy-germacran-8,12-olide ( 14 ) 9 , 19 , 20 , 26 by comparison of their MS, 1 H NMR, and 13 CNMR spectral with reported data. The conclusions were also confirmed by the 1 H- 1 H COSY, HSQC, HMBC, and NOESY spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 10 – 14 were identified as (2 S , 4 R , 5 R , 6 R , 7 S , 8 S , 9 R , 10 S , 2″ R ) -2,5-epoxy-5,10-dihydroxy-6-angeloyloxy-9-2-methylbutyryloxy-germacran-8,12-olide ( 10 ) 14 , 25 , 26 , (2 S , 4 R , 5 R , 6 R , 7 S , 8 S , 9 R , 10 S , 2″ S )-2,5-epoxy-5,10-dihydroxy-6-angeloyloxy-9-2-methylbutyryloxy-germacran-8,12-olide ( 11 ) 14 , 25 , 26 , (2 S , 4 R , 5 R , 6 R , 7 S , 8 S , 9 R , 10 S )-2,5-epoxy-5,10-dihydroxy-6-angeloyloxy-9-angeloyloxy-germacran-8,12-olide ( 12 ) 8 , 14 , 25 , 26 , 2 α ,5-epoxy-5,10-dihydroxy-6 α -angeloyloxy-9 β -3-methylbutyryloxy-germacran-8,12-olide ( 13 ) 18 20 , 25 , 26 , and 2 α ,5-epoxy-5,10-dihydroxy-6 α -angeloyloxy-9 β -isobutyryloxy-germacran-8,12-olide ( 14 ) 9 , 19 , 20 , 26 by comparison of their MS, 1 H NMR, and 13 CNMR spectral with reported data. The conclusions were also confirmed by the 1 H- 1 H COSY, HSQC, HMBC, and NOESY spectra.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, compounds 10 and 11 were usually reported as a mixture from C. triste 25 , 26 . Although both of them were separated successfully in the literature 14 , the NMR data have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…1A) was isolated from the airdried whole plant of Carpesium triste var. manshuricum (950 g) as described previously (Kim et al 2007). Test material was dissolved in DMSO; the final concentration of DMSO in cell culture media was less than 0.1%.…”
Section: Test Materialsmentioning
confidence: 99%
“…manshuricum, which is used in folk medicine in Korea as an antipyretic, analgesic, and anti-inflammatory treatment. Recent studies indicate that EDAG shows cytotoxic activity against several cancer cells (Kim et al 1999;Kim et al 2007). However, the effect of EDAG on nitric oxide synthase and its molecular mechanism has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The parent nucleus of the germacranes contains a special ten member ring with different post-modification to produce diverse structural features. A survey of the literature has shown that a large number of germacranolides are isolated from the genus Carpesium , but their absolute configurations have rarely been reported67812131920212223.…”
mentioning
confidence: 99%